Learning by Listening with Plants - Cláudia Martinho (Journal of Science and Technology of the Arts, 2021)
This review of Monica Gagliano's book Thus Spoke the Plant: A Remarkable Journey of Groundbreaking Scientific Discoveries and Personal Encounters with Plants presents the author's unconventional scientific approach to plant ecology as a human-plant collaborative endeavour. As Gagliano's personal encounters with plants supported by indigenous wisdom changed her way of doing science, the scientist learned to think out and away from the conventional box of scientific determinism and abstraction from the subjective experience. Gagliano's journey led to groundbreaking scientific discoveries in acoustic communication with plants, probing their consciousness and capacities to listen, learn and remember. This book is an important contribution not only to the field of plant bioacoustics but also to any kind of academic work, revealing that a transformative knowledge lies in collaborative ventures with nonhumans as conscious subjects in their own rights. Learning by listening with plants, a common practice in indigenous cultures, is certainly a way to engage an active dialogue with nonhuman intelligences, but we must be willing to open our minds and transcend the view of plants as objects of scientific materialism.